Optimization of the Simultaneous determination Conditions of Aflatoxins (B1, B2, G1, and G2) by High-Performance Liquid Chromatography (HPLC) with on-line photochemical derivatization and fluorescence detector (Damascus University Journal for the basic sciences, 2021)
Optimal Conditions for the determination of Aflatoxins (B1, B2, G1, G2), using High-Performance Liquid Chromatography with on-line photochemical derivatization and florescence detector (HPLC-FLD).The four Aflatoxins were separated using a C18 column eluted with an isocratic mobile phase consisting of water:methanol:acetonitrile (60:20:20 V:V:V) respectively, and flow rate (1ml/min), at a column temperature of 40ºC, with good selectivity and suitable retention time (B1 Rt=10.867 min, B2 Rt=9.027 min, G1 Rt=8.137 min, G2 Rt=6.951 min). at wavelength of the detector at 365 nm excitation and 435 nm emission for all Aflatoxins, and the total analysis time did not exceed 13 minutes. Direct photochemical derivatization achieved better results for its sensitivity, linearity, selectivity, precision and ruggedness and good separation quality compared to other derivation methods, thus HPLC-FLD can be adopted in routine quality control analysis.
Keywords: AFB1; AFB2; AFG1; AFG2; determination; HPLC; RP-HPLC; Photochemical Derivatization; fluorescence detector